Efficacy and tolerability of anti‐epileptic drugs—an internet study. (18th October 2016) - Wieshmann, U. C.; Baker, G.
Abstract : Objective: To ascertain efficacy and tolerability of carbamazepine (CBZ), sodium valproate (VPA), lamotrigine (LTG) and levetiracetam (LEV) using the UKAED register (www.ukaed.info ). Methods: Patients on CBZ (n=91), VPA (n=61), LTG (n=105), LEV (n=72) and healthy control subjects (CTR) on no medication (n=51) were extracted. All patients had anonymously provided information on seizure type and frequency and completed the Liverpool Adverse Event Profile (LAEP). Results: The number of seizure‐free patients in the last 4 weeks was overall CBZ/VPA/LTG/LEV=60%/79%/67%/67%, for generalized epilepsy was CBZ/VPA/LTG/LEV=67%/89%/65%/94%, and for localization‐related epilepsy was CBZ/VPA/LTG/LEV=59%/71%/67%/57%. Mean LAEP scores were CBZ/VPA/LTG/LEV/CTR=42.21/39.66/39.86/43.01/29.69. The mean LAEP was significantly higher in patients reporting depression and in patients with active epilepsy than in patients without depression and remission. Central nervous system (CNS) adverse effects including memory problems, difficulty concentrating, depression, unsteadiness, restlessness, feelings of anger, shaky hands and dizziness were significantly more frequent in CBZ, VPA, LTG and LEV than in CTR. The feeling of anger was significantly more frequent in LEV, and depression was significantly more frequent in CBZ compared to the other drugs. Conclusion: In this Internet‐based register of self‐reported efficacy and tolerability, CBZ, VPA, LTG and LEV were similar. Self‐reported CNS adverse effects were significantly more frequent than in controls. In addition, anger was associated with LEV and depression with CBZ. Confounding factors were depression and uncontrolled epilepsy.